Subject institute prevent bankruptcy (insolvency) - Радзивілюк, Валерія Вікторівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
The report disclosed the issue of determining a circle of relations and attributes that are the subject of the institute to prevent bankruptcy (insolvency).